Generation of Mature Murine Monocytes from Heterogeneous Bone Marrow and Description of Their Properties - Francke, Alexander (SAGE Publications, 2011)
Monocytes are involved in a wide range of physiological and pathological processes, many of which are studied in mouse models. Current protocols to isolate murine monocytes are few and result in unsatisfactory cell yield and purity. Here, we describe a novel approach to efficiently differentiate large numbers of mature inflammatory monocytes from heterogeneous bone marrow cell suspensions. Bone marrow cell suspensions were isolated by flushing femurs and tibias from Balb/c and C57Bl/6 mice, supplemented with macrophage colony–stimulating factor (M-CSF), and were cultured on ultra-low attachment surfaces to inhibit adherence-mediated maturation. Cells were harvested at indicated time points, underwent time-line analysis of the differentiation processes, and were subsequently extensively phenotyped to verify their monocytotic properties. In order to confirm downstream compatibility, we tested for typical monocyte behavior. Our protocol yielded 24 ± 6 × 10(6) differentiated cells per donor mouse, 10-fold higher than yields obtained using previously described peripheral blood isolation methods. Differentiated cells consisted of approximately 47% ± 12% monocytes, the rest being mature macrophages. We increased monocyte purity to 86% ± 6% by depleting adherent macrophages. Our findings indicate that bone marrow–derived monocytes (BMDMs) are an attractive tool to study, for example, the innate and adaptive immune system, atherosclerosis, and cellular migration during infection. Moreover, BMDM transplantation could be used to test novel, therapeutic in vivo approaches in mice disease models.